Experimental study on boron distribution and transport at plasma-facing components during impurity powder dropping in the Large Helical Device. (1st December 2022) - Kawate, T.; Ashikawa, N.; Goto, M.; Oishi, T.; Kawamoto, Y.; Toyoda, H.; Shoji, M.; Kawamura, G.; Masuzaki, S.; Nespoli, F.; Gilson, E.P.; Lunsford, R.; et al.
Abstract: Toward real-time wall conditioning, impurity powder dropping experiments with boron powder were performed in the 22nd experimental campaign of the Large Helical Device. To examine the deposition and desorption process of boron, we focus on boron hydride (BH) molecules which presumably populate near plasma-facing components. We performed spatially-resolved spectroscopic measurements of emission by boron ions and BH molecules. From the measurement, we found that BH and B + were concentrated on the divertor viewing chord, which suggest boron deposition in the divertor region. By comparing H γ emissions with and without boron injection, neutral hydrogen shows uniform reduction in the SOL region, whereas less reduction of neutral hydrogen is confirmed in the divertor region. Although emissions from BH and B + increased linearly, emissions by B 0 and B 4+ became constant after the middle of the discharge. Continuous reduction of carbon density in the core plasma was confirmed even after B 0 and B 4+ became constant. The results may show reduction of hydrogen recycling and facilitation of impurity gettering by boron in the divertor region and thus effective real-time wall conditioning.